Fundamental understanding and future guidance for handheld computers in the rail industry - Dadashi, Yasamin (2009)
Advances in mobile computing technology and software applications have led to an expansion in potential uses for handheld computers for various tasks. One strong application area is in maintenance and inspection. Network Rail has been progressively developing and applying handheld computers to field-based maintenance and inspection operations, with the aims of improving work productivity and quality, and personal and system safety. However, it is clear that these aims so far have been achieved with varying degrees of success.